"Haven't I Told You Not to Take Yourself outside of the Law?": Rabbi Yirmiyah and the Characterization of a Scholastic. Issue 2 (November 2020) - Wolf, Sarah
Abstract: The paper looks at several episodes in which R. Yirmiyah is rebuked for questions that are portrayed as epistemologically destabilizing to the rabbinic legal project. I argue that R. Yirmiyah is portrayed as a caricature of late rabbinic scholastic thought, and that his characterization enables the writers of the Bavli to hold their own scholastic tendencies up to critique while also drawing protective boundaries around the analytical direction their legal culture has taken. I also read the passages together to demonstrate that the Bavli functions as a unified literary work in previously unacknowledged ways. These episodes form a sort of nonlinear plot, a web of stories that produce a character with his own "history." There may be no historical rabbinic nuisance named R. Yirmiyah, but there is certainly a constructed literary one, whose reappearance throughout the Talmud plays an important role in working out tensions within the rabbinic legal project.